Water Absorption, Impact Resistance and Strength Reliability of Concrete Incorporating Sintered Fly Ash Aggregate Under Drop Weight Impact Load - Ranjith Babu BASKARAN; M. NAGARAJAN (Engineering Transactions, 2023)
ASTM and ACI methods were used to determine the water absorption and impact resistance of M30 grade concrete containing different percentages of sintered fly ash aggregate (SFA) ranging from 20%, 40%, 60%, 80%, and 100%. In the concrete laboratory, the parameters of the concrete mix, including fresh density, slump value, dry density, compressive strength, and impact resistance, were determined. The fresh and dry densities of concrete mix decrease as the quantity of SFA used as substitute increases. The 100% substitution of SFA in concrete results in a slump value of 200 mm, a fresh density of 1946 kg/m3, a dry density of 1911 kg/m3, and water absorption of 3.5%, with a compressive strength of 12.3 MPa. For the drop weight impact resistance test, reliability analysis was conducted to determine the level of reliability of each concrete mix for varying SFA. Using reliability analysis, the failure analysis owing to impact load determined the energy absorption of the concrete mix.